Long‐term trends in the somatic and motor characteristics of female students at the University of Warmia and Mazury in Olsztyn, Poland (2000–2018). Issue 2 (28th March 2021) - Podstawski, Robert; Żurek, Piotr
Abstract: Aim: The aim of this study was to describe changes in the anthropometric and motor characteristics of female students attending the University of Warmia and Mazury in Olsztyn between 2000 and 2018. Materials and methods: A total of 4046 randomly selected female university students aged 19–21 years (20.1 ± 1.2) were investigated. The students' body mass and height were measured, and their motor abilities were analyzed in 13 tests. Linear and curvilinear functions were fit to empirical data to assess the evaluated traits. Results: The results of the long‐term study indicate that the body height of female students increased by 3.07 cm between 2000 and 2018. A decrease in the participants' body mass and BMI was noted between 2000 and 2006 (by 0.24 kg and 0.18 kg/m 2 per year on average), whereas an increase was observed between 2006 and 2018 (by 0.34 kg and 0.10 kg/m 2 per year on average). The tested motor abilities were highly correlated with body mass, BMI and, partially, with body height. The students' motor abilities continued to improve until 2006, after which they declined steadily up to 2018 when the lowest results were noted in motor tests. Conclusions: The body height of the studied population continued to increase over the years, but it increased at a slower rate than body mass and BMI. Lower body mass and BMI values were correlated with improved scores in motor tests, whereas higher values of both parameters were accompanied by a significant decrease in all analyzed motor abilities.